Quantum dots coated with blue light absorbing layer and preparation method thereof

By forming a core-shell structure on the surface of the quantum dot, especially the combination of alloy core and multi-layer shell, the color purity and stability problems of existing quantum dot materials are solved, and efficient luminescence and high-temperature water and oxygen insulation properties are achieved, and it is suitable for light emitting diodes and other fields.

CN117025223BActive Publication Date: 2025-09-02NAN PAO RESINS CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310494887.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-05
Publication Date
2025-09-02
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The existing quantum dot materials have dimensional inconsistencies, resulting in insufficient color purity and low luminous efficiency, and insufficient temperature resistance and water and oxygen insulation performance, which affects the stability of the application device.

Method used

A core-shell luminescent quantum dot structure is adopted, in which the alloy core consists of cadmium, selenium, zinc and sulfur, and the outer layer is coated with a first shell with a sphalerite structure and a second shell with a wurtzite structure, and is formed by a specific preparation method.

Benefits of technology

It improves luminous efficiency and color purity, enhances water and oxygen insulation performance and high temperature resistance, extends service life, and improves the stability of quantum dots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117025223B_ABST
    Figure CN117025223B_ABST
Patent Text Reader

Abstract

The present disclosure provides a quantum dot coated with a blue light absorbing layer and a preparation method thereof. Specifically, the present disclosure provides a luminescent quantum dot coated with at least one blue light absorbing layer, comprising an alloy core composed of cadmium, selenium, zinc and sulfur, a first shell having a sphalerite structure and coated on the surface of the alloy core, and at least one second shell having a wurtzite structure, wherein the elemental proportions of zinc and sulfur each account for 30 to 50% of the entire core, and the content of cadmium and selenium decreases from the center of the core to the outside. The present disclosure also provides a method for preparing the core-shell type luminescent quantum dot. Through the alloy core, the first shell having a sphalerite structure and the second shell having a wurtzite structure, the core-shell type quantum dot can achieve a quantum efficiency of more than 95%, and has high temperature resistance and excellent water and oxygen isolation properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to quantum dots and a method for preparing the same, and in particular to luminescent quantum dots comprising at least one blue light absorbing layer and a method for preparing the same. Background Art

[0002] Quantum dots are nanometer-sized particles. Because their size is less than twice the Bohr exciton radius of an electron, they experience quantum confinement, forming discontinuous energy bands. Consequently, quantum dots exhibit the characteristic of spontaneous fluorescence upon excitation. The optoelectronic properties resulting from this unique effect have led to their widespread application in light-emitting diodes, solar cells, photodetectors, liquid crystal displays, color enhancement films, and color filters.

[0003] However, existing quantum dot materials suffer from issues such as insufficient color purity and low luminous efficiency due to difficulties in controlling their dimensional consistency. Furthermore, existing quantum dots are not resistant to high temperatures and have insufficient water and oxygen barriers, which affects the stability of applied devices and limits the material's widespread adoption.

[0004] Therefore, there is a need for a luminescent quantum dot with high luminous efficiency, high color purity, good water and oxygen isolation properties and good temperature resistance. Summary of the Invention

[0005] The present disclosure provides a core-shell type luminescent quantum dot, which includes: an alloy core composed of cadmium, selenium, zinc and sulfur, wherein the elemental ratio of zinc and sulfur each accounts for 30% to 50% of the entire core, and the content of cadmium and selenium decreases from the center of the alloy core outward; a first shell layer having a zinc blende structure, which is coated on the surface of the alloy core, and the first shell layer is composed of zinc sulfide; and at least one second shell layer having a wurtzite structure, which is coated on the surface of the first shell layer.

[0006] In one embodiment of the present disclosure, the luminescent quantum dots have a D90 particle size of 16 to 18 nm, and the alloy core has a radius of 3 nm or less.

[0007] In one embodiment of the present disclosure, the at least one second shell layer is composed of cadmium, selenium, zinc and sulfur. In another embodiment of the present disclosure, the cadmium, selenium, zinc and sulfur of the at least one second shell layer have a molar ratio of 1:20:6:3 to 1.2:28:12:6.

[0008] In one embodiment of the present disclosure, the cadmium, selenium, zinc and sulfur of the light-emitting quantum dots have a molar ratio of 0.03:1:1:1 to 0.05:1.1:1.1:1.3. In another embodiment of the present disclosure, the zinc, sulfur and selenium of the light-emitting quantum dots have a molar ratio of 0.9:0.9:1 to 1.2:1.5:1.

[0009] In one embodiment of the present disclosure, the elemental ratios of zinc and selenium in the luminescent quantum dots are each 25% to 40% of the core-shell type luminescent quantum dots, the elemental ratio of sulfur is 30% to 50% of the core-shell type luminescent quantum dots, and the elemental ratio of cadmium is 0.3% to 5% of the core-shell type luminescent quantum dots. In this embodiment, the elemental ratio of cadmium in the luminescent quantum dots is 0.3% to 3% of the core-shell type luminescent quantum dots.

[0010] In one embodiment of the present disclosure, the element ratio of cadmium and selenium each accounts for 3% to 10% of the entire core.

[0011] The present disclosure also provides a method for preparing core-shell type luminescent quantum dots, which includes: providing a first metal precursor solution containing a cadmium metal precursor and a zinc metal precursor, and activating the first metal precursor solution with a reactive amine; mixing a first ion stock solution containing sulfide ions and selenium ions, and reacting the first ion stock solution with the activated metal precursor solution containing the cadmium metal precursor and the zinc metal precursor to obtain a solution containing an alloy core; adding a second ion stock solution containing sulfide ions and a zinc salt to the solution containing the alloy core for reaction, thereby forming a first shell layer coated on the surface of the alloy core; adding a second metal precursor solution containing a cadmium metal precursor and a zinc metal precursor to the solution containing the alloy core coated with the first shell layer; mixing a third ion stock solution containing selenium ions with the solution containing the alloy core coated with the first shell layer and the second metal precursor for reaction; and adding dodecanethiol to the solution containing the third ion stock solution to form a second shell layer coated on the surface of the first shell layer.

[0012] In one embodiment of the disclosed method, the activated first metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor is prepared by a process comprising activating the cadmium metal precursor with a reactive amine and a reactive acid.

[0013] In one embodiment of the method of the present disclosure, the process further includes: providing a first metal precursor solution comprising a cadmium metal precursor, wherein the cadmium metal precursor is activated with a reactive amine and a reactive acid in the first metal precursor solution comprising the cadmium metal precursor; and adding a zinc metal precursor to the activated first metal precursor solution comprising the cadmium metal precursor to activate the zinc metal precursor at a temperature of 300°C to 320°C.

[0014] In one embodiment of the method of the present disclosure, the process further includes: providing a first metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor, wherein the cadmium metal precursor is activated with a reactive amine and a reactive acid in the first metal precursor solution comprising the cadmium metal precursor and the zinc metal precursor; and heating the activated first metal precursor solution comprising the cadmium metal precursor and the zinc metal precursor to a temperature of 300° C. to 320° C. to activate the zinc metal precursor.

[0015] In one embodiment of the disclosed method, the reactive acid is oleic acid and the reactive amine is a primary amine. In this embodiment of the disclosed method, the molar ratio of the reactive amine to the reactive acid is from 1:7 to 1:7.5. In another embodiment of the disclosed method, the primary amine is selected from the group consisting of oleylamine, hexadecanamine, pentadecylamine, and dodecylamine.

[0016] In one embodiment of the disclosed method, the process further comprises: heating the second metal precursor solution to a temperature of 180° C. to 240° C. and maintaining the temperature for 10 to 30 minutes to activate the cadmium metal precursor and the zinc metal precursor in the second metal precursor solution. In another embodiment of the disclosed method, the second metal precursor solution further comprises octadecenoic acid, and the cadmium metal precursor and the zinc metal precursor are dissolved in the octadecenoic acid.

[0017] In one embodiment of the disclosed method, the activated second metal precursor solution is heated to a temperature of 270° C. to 310° C. before being mixed with the third ion stock solution.

[0018] In one embodiment of the disclosed method, a nitrogen purge step is performed with N2 when activating the cadmium metal precursor and the zinc metal precursor.

[0019] In one embodiment of the method of the present disclosure, the solution containing the alloy core is obtained by reacting at a temperature of 280° C. to 310° C. for 10 to 20 minutes.

[0020] In one embodiment of the method of the present disclosure, adding the second ion stock solution comprising sulfide ions and zinc salt further comprises: adding the second ion stock solution comprising sulfide ions to the solution containing the alloy core and maintaining the solution for 15 to 20 minutes; and adding the zinc salt to react for 20 to 30 minutes.

[0021] In one embodiment of the disclosed method, the zinc salt is zinc oleate.

[0022] In one embodiment of the disclosed method, the first shell layer is formed at a reaction temperature of 240°C to 270°C, and the second shell layer is formed at a reaction temperature of 270°C to 310°C.

[0023] In one embodiment of the disclosed method, the cadmium metal precursor, the zinc metal precursor, the sulfide ions, and the selenium ions used to obtain the solution containing the alloy core have a molar ratio of 0.14:5.9:4.2:1.5 to 1:5.9:4.2:1.5.

[0024] In one embodiment of the disclosed method, the reactive amine, cadmium metal precursor, and zinc metal precursor used to form the alloy core coated with the first shell layer have a molar ratio of 3:0.14:5.9 to 3:1:5.9.

[0025] In one embodiment of the disclosed method, the molar ratio of the cadmium metal precursor, the zinc metal precursor, dodecanethiol, and the selenium ion used to form the second shell layer has a molar ratio of 0.65:5.4:50:24 to 1.3:10.8:70:48.

[0026] In one embodiment of the disclosed method, the cadmium metal precursor is selected from at least one of cadmium oxide and cadmium acetate (Cd(ac)2). The zinc metal precursor is selected from at least one of zinc oxide and zinc acetate (Zn(ac)2).

[0027] Based on the preparation method disclosed herein, the core-shell type luminescent quantum dots contain a shell layer having a wurtzite structure and composed of cadmium, selenium, zinc and sulfur, which can provide effective protection for the alloy core, improve the stability of the core-shell type luminescent quantum dots and extend their service life. In addition, the second shell layer having a wurtzite structure formed on the surface of the core-shell type luminescent quantum dots can increase the absorption of blue light, has high temperature resistance and excellent water and oxygen isolation properties. In addition, the core-shell type luminescent quantum dots have a second shell layer with a wurtzite structure and a lower half-maximum width (FWHM), which can improve the color performance and luminescent color purity of the quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The embodiments of the present disclosure are described by way of example with reference to the accompanying drawings:

[0029] Figure 1A A schematic diagram of the structure of quantum dots in the prior art;

[0030] Figure 1B The structure of the core-shell type light-emitting quantum dots according to one embodiment of the present disclosure is exemplified;

[0031] Figure 1C The structure of a core-shell type light-emitting quantum dot according to another embodiment of the present disclosure is exemplarily shown;

[0032] Figures 2A to 2CThe particle size distribution diagrams of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure are shown respectively;

[0033] Figures 3A to 3C The figures show photographs of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure observed by high-resolution transmission electron microscopy (HRTEM);

[0034] Figures 4A to 4C Elemental diagrams of sulfur, zinc, selenium, and cadmium are shown for the entire luminescent quantum dots of Comparative Example 1 and the entire core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure, respectively, analyzed by energy dispersive X-ray spectroscopy (EDS);

[0035] Figure 5 Graphs showing the element molar ratio (%) of the entire luminescent quantum dots of Comparative Example 1 and the entire core-shell type luminescent quantum dots of Examples 1 and 2 of the present disclosure, respectively;

[0036] Figure 6 The X-ray diffraction patterns (XRD) of the luminescent quantum dots of Comparative Example 1 and the core-shell type luminescent quantum dots of Example 1 of the present disclosure are shown;

[0037] Figure 7A and Figure 7B Elemental diagrams of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 of the present disclosure are respectively shown by line scanning of energy dispersive spectroscopy (EDS) analysis;

[0038] Figure 8A and Figure 8B The figures show photographs of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 of the present disclosure observed by high-resolution transmission electron microscopy (HRTEM).

[0039] Figure 9 Absorption spectra of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure measured by ultraviolet-visible light (UV-Vis) absorption spectrophotometry at a wavelength of 400 to 600 nm are shown respectively;

[0040] Figure 10 Graphs showing the full width at half maximum (FWHM) of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 of the present disclosure measured by photoluminescence spectroscopy are shown respectively;

[0041] Figure 11The absorption spectra of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure at a wavelength of 450 nm, measured by ultraviolet-visible light (UV-Vis) absorption spectrophotometry at a wavelength of 400 to 600 nm, are shown respectively;

[0042] Figure 12 The normalized intensities of the optical films prepared from the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure are respectively shown, measured at a relative humidity of 65% and a temperature of 90° C. for 1000 hours;

[0043] Figure 13 and Figure 14 The normalized intensities of the green and red optical films prepared from the core-shell luminescent quantum dots of Example 1 of the present disclosure are shown respectively, and the intensities are measured at a relative humidity of 65% and a temperature of 90° C. for 1000 hours;

[0044] Figure 15 The brightness-voltage curves of light-emitting diodes prepared using the green thin-shell quantum dots of the prior art, the green quantum dots of Comparative Example 1, and the green core-shell quantum dots of Example 1 of the present disclosure are shown respectively;

[0045] Figure 16 The external quantum efficiency (EQE)-voltage curves of light-emitting diodes prepared using the green thin-shell quantum dots of the prior art, the green quantum dots of Comparative Example 1, and the green core-shell luminescent quantum dots of Example 1 of the present disclosure are shown respectively;

[0046] Figure 17 The external quantum efficiency (EQE)-brightness curves of light-emitting diodes prepared using the green thin-shell quantum dots of the prior art, the green quantum dots of Comparative Example 1, and the green core-shell luminescent quantum dots of Example 1 of the present disclosure are shown respectively.

[0047] Description of Reference Numerals

[0048] 1 Luminescent quantum dots

[0049] 11 Alloy Core

[0050] 12 Shell

[0051] 2 Core-shell luminescent quantum dots

[0052] 21 Alloy Core

[0053] 22 First Shell

[0054] 23 Second Shell

[0055] 3 Core-shell luminescent quantum dots

[0056] 31 Alloy Core

[0057] 32 First Shell

[0058] 33 Second Shell

[0059] 34 Another second shell. DETAILED DESCRIPTION

[0060] The following describes the embodiments of the present disclosure through specific specific examples. Those skilled in the art to which the present disclosure belongs can easily understand the advantages and effects of the present disclosure based on the contents disclosed herein. However, the embodiments described herein are not intended to limit the present disclosure. The present disclosure can also be implemented or applied through other different embodiments. The various details described herein can also be given different changes or modifications based on different viewpoints and applications without departing from the scope of the present disclosure. In addition, all ranges and values ​​herein are inclusive and combinable. Any numerical value or point falling within the range described herein, such as any integer, can be used as a minimum value or maximum value to derive a lower range, etc.

[0061] refer to Figure 1A A schematic diagram of the structure of a prior art luminescent quantum dot is shown. The luminescent quantum dot 1 comprises an alloy core 11 composed of cadmium, selenium, zinc, and sulfur, with zinc and sulfur each accounting for 30% to 50% of the core, while the cadmium and selenium content decreases from the center of the core outward; and a zinc blende shell 12 coating the surface of the luminescent core.

[0062] Figure 1B and Figure 1C The structure of the core-shell type luminescent quantum dots of different embodiments of the present disclosure is shown. Figure 1B As shown, the core-shell type luminescent quantum dot 2 includes: an alloy core 21 composed of cadmium, selenium, zinc and sulfur, with the proportion of zinc and sulfur elements each accounting for 30% to 50% of the entire core, and the content of cadmium and selenium decreasing from the center of the core to the outside; a first shell layer 22 composed of zinc sulfide coated on the surface of the luminescent core; and a second shell layer 23 with a wurtzite structure coated on the first shell layer 22. Figure 1C The core-shell luminescent quantum dot 3 shown includes: an alloy core 31 composed of cadmium, selenium, zinc and sulfur, with the zinc and sulfur elements each accounting for 30% to 50% of the entire core, and the cadmium and selenium contents decreasing from the center of the core to the outside; a first shell layer 32 composed of zinc sulfide coated on the surface of the luminescent core; a second shell layer 33 with a wurtzite structure coated on the first shell layer 32; and another second shell layer 34 with a wurtzite structure coated on the second shell layer 33.

[0063] Hereinafter, the present disclosure will be described in more detail with reference to the following preparation examples and examples. However, these preparation examples and examples are provided only to illustrate the present disclosure, and the scope of the present disclosure is not limited thereto.

[0064] Comparative Example 1

[0065] 1 ml of octadeceneamine and 7 ml of octadecene acid were added to the first metal precursor solution containing 0.14 mmol of cadmium, and the cadmium metal precursor was activated at a temperature of 310°C.

[0066] Next, 2.9 mmol of zinc metal precursor was added to the cadmium metal precursor solution, and the zinc metal precursor was activated at a temperature of 310°C.

[0067] Next, a first ion stock solution containing 2.2 mmol of sulfur, 1.5-2.9 mmol of selenium, and 3 ml of trioctylphosphine (TOP) was prepared. The first ion reserve solution was then added to a solution containing activated cadmium and zinc metal precursors at a temperature of 280°C to 310°C to initiate a reaction. After 10 to 20 minutes of reaction, a solution containing alloyed luminescent core particles was produced.

[0068] In addition, a second ion stock solution containing 2 mmol of sulfur and 1 ml of TOP was prepared, and then the second ion stock solution was added to the solution containing the alloy core and reacted at a temperature of 240° C. to 270° C. for 15 to 20 minutes.

[0069] After reacting for 15 to 20 minutes, 3 mmol of zinc octadecenoate is added at a temperature of 240° C. to 270° C. and the reaction is continued for 20 to 30 minutes to obtain luminescent quantum dots comprising an alloy core of cadmium selenide zinc sulfur (CdSeZnS) and a shell layer of zinc sulfide sphalerite structure.

[0070] Example 1

[0071] The preparation method of Example 1 is the same as that of Comparative Example 1, but this example further includes a process for generating a second shell layer on the surface of the first shell layer.

[0072] A second metal precursor solution containing 0.65 mmol of cadmium and 0.54 mmol of zinc dissolved in 11 ml of octadecenoic acid was added to a solution of luminescent quantum dots containing a cadmium-selenium-zinc-sulfur alloy core and a zinc sulfide shell. The second metal precursor solution was activated at 270°C under a nitrogen purge for 10 to 20 minutes.

[0073] In addition, a third ion stock solution containing 0.024 mol of selenium and 0.053 mol of TOP was prepared, and then added to the solution containing the luminescent quantum dots and the second metal precursor, and reacted at a temperature of 270° C. to 310° C. for 10 to 30 minutes.

[0074] After reacting for 10 to 30 minutes, 0.05 mol of dodecanethiol is added at a temperature of 270° C. to 310° C. and the reaction is continued for 10 to 30 minutes to obtain core-shell type luminescent quantum dots having a cadmium selenium zinc sulfur alloy core, a first shell layer of zinc sulfide and a second shell layer of a cadmium selenium zinc sulfur wurtzite structure.

[0075] Example 2

[0076] The preparation method of Example 2 is the same as that of Example 1, but this example also includes a process for generating another second shell layer on the surface of the second shell layer. In other words, the core-shell luminescent quantum dots obtained in Example 2 have a cadmium-selenium-zinc-sulfur alloy core, a zinc sulfide first shell layer, and a two-layer cadmium-selenium-zinc-sulfur wurtzite second shell layer.

[0077] The luminescent quantum dots prepared above were analyzed by a particle size analyzer. Figures 2A to 2C As shown, the particle size of the luminescent quantum dots D90 of Comparative Example 1 is 15.4 nm, and the standard deviation of its average particle size is 1.43 nm; the particle size of the luminescent quantum dots D90 of Example 1 is 16.8 nm, and the standard deviation of its average particle size is 1.70 nm; and the particle size of the luminescent quantum dots D90 of Example 2 is 17.6 nm, and the standard deviation of its average particle size is 1.61 nm.

[0078] The luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 were observed by high-resolution transmission electron microscopy (HRTEM). Figure 3A As shown, the luminescent quantum dots of Comparative Example 1 have a polygonal appearance and have several sharp corners. Figure 3B and Figure 3C The core-shell luminescent quantum dots of Examples 1 and 2 have an irregular appearance.

[0079] Furthermore, the luminescent quantum dots were analyzed by energy dispersive X-ray spectroscopy (EDS). Figures 4A to 4C The elemental compositions of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 are shown respectively. Figure 5 The molar ratios of cadmium, selenium, zinc, and sulfur are shown for the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2. In the core-shell luminescent quantum dots of Examples 1 and 2, the molar ratios of selenium and zinc increase, while the molar ratio of sulfur decreases, due to the presence of the second shell layer.

[0080] The luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 were further analyzed by X-ray diffraction (XRD). Figure 6 As shown, the luminescent quantum dots of Comparative Example 1 have a zinc blende structure, while the core-shell luminescent quantum dots of Example 1 have a wurtzite structure.

[0081] The composition distribution of the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 was measured by X-ray diffraction (XRD). In addition, the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Example 1 were observed by high-resolution transmission electron microscopy (HRTEM). Figure 7A The cadmium, selenium, zinc and sulfur in the luminescent quantum dots of Comparative Example 1 are Gaussian distributed. Figure 7B 、 Figure 8A and Figure 8B As shown, a second shell consisting of a wurtzite structure composed of cadmium, selenium, zinc and sulfur is indeed produced on the outer shell of the first shell composed of zinc sulfide.

[0082] The absorbance (ie, optical density OD) of the above-mentioned luminescent quantum dots is measured by ultraviolet-visible (UV-Vis) absorption spectrophotometry. Figure 9 and Figure 11 As shown, the absorbance of the core-shell type luminescent quantum dots coated with at least one second shell layer at a wavelength of 400 to 600 nm is higher than that of the core-shell type luminescent quantum dots containing an alloy core and a zinc blende structure shell layer.

[0083] refer to Figure 10 The luminescent quantum dots of Comparative Example 1 exhibited a 22nm half-maximum width (FWHM) emission, while the core-shell luminescent quantum dots of Example 1 exhibited a 19nm FWHM emission. The reduced FWHM indicates improved color performance and luminescent color purity in subsequent applications.

[0084] An optical film containing the above-mentioned luminescent quantum dots was prepared to perform the following strength tests.

[0085] The strength of the optical film prepared from the luminescent quantum dots of Comparative Example 1 and the core-shell luminescent quantum dots of Examples 1 and 2 of the present disclosure was measured at a relative humidity of 65% and a temperature of 90°C for 1000 hours. Furthermore, the strength of the green optical film and the red optical film prepared from the core-shell luminescent quantum dots of Example 1 was measured under the same conditions. Figures 12 to 14 As shown, the normalized intensity of the core-shell luminescent quantum dots coated with at least one second shell layer (ie, Examples 1 and 2) is still 99% after 1000 hours in a high temperature and high relative humidity environment.

[0086] The green thin-shell quantum dots of the prior art, the green quantum dots of Comparative Example 1, and the core-shell green quantum dots of Example 1 of the present disclosure were further prepared into light-emitting diodes. The structure of the light-emitting diode is in sequence: indium tin oxide glass, magnesium zinc oxide with a thickness of about 40 nm, quantum dots, tris(4-carbazolyl-9-phenyl)amine (TCTA) with a thickness of about 70 nm, manganese oxide with a thickness of about 10 nm, and aluminum with a thickness of about 100 nm. The brightness-voltage curve, external quantum efficiency (EQE)-voltage curve, and external quantum efficiency (EQE)-brightness curve of the light-emitting diodes prepared with the green thin-shell quantum dots of the prior art, the green quantum dots of Comparative Example 1, and the core-shell green quantum dots of Example 1 of the present disclosure are shown in FIG. Figures 15 to 17 .

[0087] In addition, the properties of the aforementioned light emitting diodes are listed in Table 1 below.

[0088] Table 1

[0089]

[0090] like Figures 15 to 17 As can be seen from Table 1, the core-shell luminescent quantum dots coated with at least one second shell layer composed of cadmium, selenium, zinc and sulfur and having a wurtzite structure exhibit improved optical properties in light emission.

[0091] From the above, it can be seen that the preparation method described in the present disclosure can provide core-shell type luminescent quantum dots composed of cadmium, selenium, zinc and sulfur and having a wurtzite structure shell, which can effectively protect the alloy core, improve the stability of the core-shell type luminescent quantum dots and extend their service life.

[0092] In addition, the core-shell luminescent quantum dots containing a second shell layer with a wurtzite structure can increase the absorption of blue light, are resistant to high temperatures, and have excellent water and oxygen isolation properties.

[0093] By combining an alloy core with a zinc blende shell, the resulting core-shell quantum dots can achieve a quantum efficiency of 95%, significantly reducing power consumption and thus achieving significant energy savings. Therefore, the core-shell quantum dots disclosed herein have industrial application value.

[0094] The above embodiments are intended to be illustrative only and are not intended to limit the present disclosure. Any person skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present disclosure. Therefore, the scope of protection of the present disclosure is defined by the claims appended hereto. Any claims that do not affect the effectiveness and purpose of the present disclosure shall be encompassed by the technical content of this disclosure.

Claims

1. A core-shell luminescent quantum dot comprising: An alloy core composed of cadmium, selenium, zinc, and sulfur, wherein the zinc and sulfur each account for 30% to 50% of the alloy core, and the cadmium and selenium contents decrease from the center of the alloy core outward; a first shell layer having a sphalerite structure, which covers the surface of the alloy core, wherein the first shell layer is composed of zinc sulfide; and At least one second shell layer having a wurtzite structure is coated on the surface of the first shell layer, wherein the at least one second shell layer is composed of cadmium, selenium, zinc and sulfur, and the cadmium, selenium, zinc and sulfur of the at least one second shell layer have a molar ratio of 1:20:6:3 to 1.2:28:12:

6. 2 . The core-shell luminescent quantum dot according to claim 1 , having a D90 particle size of 16 to 18 nm, wherein the alloy core has a radius of 3 nm or less.

3. The core-shell type luminescent quantum dots according to claim 1, wherein the elemental proportions of zinc and selenium each account for 25% to 40% of the core-shell type luminescent quantum dots, the elemental proportion of sulfur accounts for 30% to 50% of the core-shell type luminescent quantum dots, and the elemental proportion of cadmium accounts for 0.3% to 5% of the core-shell type luminescent quantum dots. The core-shell type luminescent quantum dot according to claim 1 , wherein the element ratio of cadmium and selenium each accounts for 3% to 10% of the alloy core.

5. A method for preparing core-shell luminescent quantum dots according to claim 1, comprising: Providing a first metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor, and activating the first metal precursor solution with a reactive amine; mixing a first ion stock solution comprising sulfur ions and selenium ions, and reacting the first ion stock solution with the activated metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor to obtain a solution containing an alloy core; adding a second ion stock solution containing sulfide ions and zinc salt to the solution containing the alloy core to react, thereby forming a first shell layer covering the surface of the alloy core; adding a second metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor to the solution comprising the alloy core coated with the first shell layer; mixing a third ion stock solution containing selenium ions with the solution containing the alloy core coated with the first shell layer and the second metal precursor to react; as well as Dodecanethiol is added to the solution containing the third ion stock solution to form a second shell layer coated on the surface of the first shell layer. 6 . The method of claim 5 , wherein the activated first metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor is prepared by a process comprising activating the cadmium metal precursor with a reactive amine and a reactive acid.

7. The method of claim 6, wherein the process further comprises: providing a first metal precursor solution containing a cadmium metal precursor, wherein the cadmium metal precursor is activated with the reactive amine and the reactive acid in the first metal precursor solution containing the cadmium metal precursor; and The zinc metal precursor is added to the activated first metal precursor solution including the cadmium metal precursor to activate the zinc metal precursor at a temperature of 300°C to 320°C.

8. The method of claim 6, wherein the process further comprises: Providing the first metal precursor solution comprising a cadmium metal precursor and a zinc metal precursor, wherein the cadmium metal precursor is activated with the reactive amine and the reactive acid in the first metal precursor solution comprising the cadmium metal precursor and the zinc metal precursor; as well as The activated first metal precursor solution comprising the cadmium metal precursor and the zinc metal precursor is heated to a temperature of 300° C. to 320° C. to activate the zinc metal precursor.

9. The method according to claim 6, wherein the reactive acid is octadecenoic acid, the reactive amine is a primary amine, and the molar ratio of the reactive amine to the reactive acid is 1:7 to 1:7.

5.

10. The method according to claim 5, wherein the preparation method further comprises: heating the second metal precursor solution to a temperature of 180° C. to 240° C. and maintaining the temperature for 10 to 30 minutes to activate the cadmium metal precursor and the zinc metal precursor in the second metal precursor solution; and The second metal precursor solution further comprises octadecenoic acid, and the cadmium metal precursor and the zinc metal precursor are dissolved in the octadecenoic acid.

11. The method according to claim 10, wherein: The activated second metal precursor solution is heated to a temperature of 270° C. to 310° C. before being mixed with the third ion stock solution.

12. The method according to claim 10, wherein: During activation of the cadmium metal precursor and the zinc metal precursor, a nitrogen purge step with N2 was performed.

13. The method of claim 9, wherein the primary amine is selected from the group consisting of octadecylamine, hexadecylamine, pentadecylamine, and dodecylamine.

14. The method according to claim 5, wherein the solution containing the alloy core is obtained by reacting at a temperature of 280 to 310°C for 10 to 20 minutes.

15. The method according to claim 14, wherein adding the second ion stock solution comprising sulfide ions and zinc salt further comprises: adding a second ion stock solution comprising sulfide ions to the solution containing the alloy core and maintaining the solution for 15 to 20 minutes; as well as The zinc salt is added and reacted for 20 to 30 minutes.

16. The method of claim 5, wherein the zinc salt is zinc octadecenoate.

17. The method of claim 5, wherein the first shell layer is formed at a reaction temperature of 240°C to 270°C, and wherein the second shell layer is formed at a reaction temperature of 270°C to 310°C.

18. The method of claim 5, wherein the reactive amine, cadmium metal precursor, and zinc metal precursor used to form the alloy core coated with the first shell layer have a molar ratio of 3:0.14:5.9 to 3:1:5.

9.

19. The method according to claim 5, wherein the cadmium metal precursor, the zinc metal precursor, the sulfide ions and the selenium ions used to obtain the solution containing the alloy core have a molar ratio of 0.14:5.9:4.2:1.5 to 1:5.9:4.2:1.5, and The cadmium metal precursor, the zinc metal precursor, dodecanethiol and selenium ions used to form the second shell layer have a molar ratio of 0.65:5.4:50:24 to 1.3:10.8:70:48.

Citation Information

Patent Citations

  • Core-shell light-emitting quantum dot material and manufacturing method thereof

    CN112779012A